Transformational Leadership Strategies For Enhancing Field Team Engagement Through Education, Empowerment, And Reward-Recognition At Pt Tekno Buana Globalindo - Panggabean, Indra; Saputra , Boby Wiryawan (Enrichment: Journal of Multidisciplinary Research and Development, 2025)
This study examines transformational leadership strategies for enhancing field team engagement at PT Tekno Buana Globalindo, a company operating in the Oil & Gas Service sector with a focus on clean water treatment and waste management. Field teams play a critical role in the company’s operational success, yet they often face challenges such as limited training, ineffective communication, lack of decision-making autonomy, and insufficiently motivating reward systems. Using a quantitative approach with an associative–explanatory design, data were collected from 146 field team members through questionnaires and interviews. The analysis was conducted using Partial Least Squares–Structural Equation Modeling (PLS-SEM) to identify relationships between transformational leadership dimensions and employee engagement. The findings reveal that transformational leadership significantly influences employee engagement indirectly through three primary pathways: education, empowerment, and reward-recognition. Education emerged as the strongest driver, highlighting the importance of structured and context-relevant training in building skills and confidence. Empowerment, when implemented progressively and supported by adequate frameworks, was found to enhance autonomy and responsibility among employees, while recognition systems required contextual redesign to strengthen motivation and reduce turnover. The study provides theoretical contributions to the literature on transformational leadership in decentralized and high-risk industries, and practical insights for managers seeking to build adaptive, engaged, and sustainable field teams.